Strategy and Policy for Empowerment of Duck Farming Business in Brebes Sub-District, Brebes Regency - Oke Setiarso; Sukiman Sukiman; Nunik Kadarwati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2017)
This study aimed to determine appropriate strategies and policies for empowerment of duck farming business in Brebes Sub-District, Brebes Regency. The method of this study was survey using stratified random sampling with the sample size of 52 laying duck farmers. Data taken in the form of primary and secondary data were analyzed using SWOT analysis. The result indicated that duck farming business did not have Economic Institutions, it was an individual, dependent and unprofessional business because it depended on the middlemen. It can be said that duck farming business in Brebes Regency was a livestock labor business. The strategies and policies for empowerment of duck farming business in Brebes sub-district Brebes Regency included the provision of livestock area facility, waste management, capital, livestock management and development of marketing centers for processed duck meat and eggs products.Keywords: Duck, Institution, Cooperation, Strategy, Policy.